A fine-tuning mechanism underlying self-control for autophagy: deSUMOylation of BECN1 by SENP3. Issue 6 (2nd June 2020) - Liu, Kejia; Guo, Chu; Lao, Yimin; Yang, Jie; Chen, Fei; Zhao, Yuzheng; Yang, Yi; Yang, Jie; Yi, Jing
ABSTRACT: The roles of SUMOylation and the related enzymes in autophagic regulation are unclear. Based on our previous studies that identified the SUMO2/3-specific peptidase SENP3 as an oxidative stress-responsive molecule, we investigated the correlation between SUMOylation and macroautophagy/autophagy. We found that Senp3 ± mice showed increased autophagy in the liver under basal and fasting conditions, compared to Senp3 +/+ mice. We constructed a liver-specific senp3 knockout mouse; these Senp3 -deficient liver tissues showed increased autophagy as well. Autophagic flux was accelerated in hepatic and other cell lines following knockdown of SENP3, both before and after the cells underwent starvation in the form of the serum and amino acid deprivation. We demonstrated that BECN1/beclin 1, the core molecule of the BECN1-PIK3C3 complex, could be SUMO3-conjugated by PIAS3 predominantly at K380 and deSUMOylated by SENP3. The basal SUMOylation of BECN1 was increased upon cellular starvation, which enhanced autophagosome formation by facilitating BECN1 interaction with other complex components UVRAG, PIK3C3 and ATG14, thus promoting PIK3C3 activity. In contrast, SENP3 deSUMOylated BECN1, which impaired BECN1-PIK3C3 complex formation or stability to suppress the PIK3C3 activity. DeSUMOylation of BECN1 restrained autophagy induction under basal conditions and especially upon starvation when SENP3 had accumulated in response to the increased generation of reactive oxygen species. Thus, while reversible SUMOylation regulated the degree of autophagy, SENP3 provided an intrinsic overflow valve for fine-tuning autophagy induction. Abbreviations: AL: autolysosome; AP: autophagosome; ATG: autophagy related; ATG14: autophagy related 14; BECN1: beclin 1, autophagy related; cKO: conditional knockout; co-IP: co-immunoprecipitation; CQ: chloroquine; EBSS: Earle's balanced salt solution; GFP: green fluorescent protein; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NAC: N-acetyl-L-cysteine; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; PTM: post-translational modification; RFP: red fluorescent protein; ROS: reactive oxygen species; RUBCN/rubicon: RUN domain and cysteine-rich domain containing, BECN1-interacting protein; SENP3: SUMO specific peptidase 3; shRNA: small hairpin RNA; siRNA: small interfering RNA; SQSTM1: sequestosome 1; SUMO: small ubiquitin-like modifier; UVRAG: UV radiation resistance associated gene.